2022
DOI: 10.1088/1742-6596/2214/1/012030
|View full text |Cite
|
Sign up to set email alerts
|

Correlating between global solar radiation and greenhouse gases over Nigeria

Abstract: The need to study the variations of climate change in Nigeria becomes necessary at a time the universe and Nigerians, in particular are passing through challenges due to climate change as a result of emissions. The atmospheric gases have a greater transparency for incoming solar radiation, while the outgoing are trapped and re-emitted back to the Earth. This study correlated between global solar radiation and greenhouse gases over Nigeria using neural network. The results showed that positive correlations exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Ref. [10] measured the internal combustion engine and its tremendous impact on pollution. Similarly, it was found that local zero-emission standards and the global climate need further renovations to reduce carbon emissions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ref. [10] measured the internal combustion engine and its tremendous impact on pollution. Similarly, it was found that local zero-emission standards and the global climate need further renovations to reduce carbon emissions.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Ref. [10] briefed that local zero-emission standards and global climate objectives need further renovations to meet these requirements and reduce carbon emissions. Ref.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ref. [11] measured the internal combustion of engine and its tremendous impact on pollution. Similarly, it is found that local zero-emission standards and global climate need further renovations to reduce carbon emissions.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Ref. [11] briefed that local zero-emission standards and global climate objectives need further renovations to meet these requirements and reduce carbon emissions. Ref.…”
Section: Literature Reviewmentioning
confidence: 99%